Miniinvasive paracentetic drain surgical interventions under ultrasonic control concerning liquid formations of abdominal cavity - G.I. Ohrimenko; N.G. Golovko; V.A. Grushka; Y.I. Gaidarzhi (Zaporozhye State Medical University, 2013)
Entry. Presently miniinvasive surgical interventions under ultrasonic control became the method of choice in treatment of quite a number of abdominal and retroperitoneal organs diseases, and their complications. These operations have a row of advantages, as compared to open and laparoscopic ones: comparative simplicity, insignificant infecting of abdominal region, least of intra- and postoperative complications. Actuality of problem is conditioned by that indications to the use of paracentetic drain surgical interventions, most optimal methods of preoperative diagnostic, features of postoperative treatment of patients remain not enough studied. Research aim. To study the results of diagnostics and treatment of patients with liquid formations of abdominal cavity that were exposed to miniinvasive surgical interventions under ultrasonic control and, on the basis of it, to work out an optimal curative diagnostic algorithm. Materials and research methods. The results of treatment of 25 patients with liquid formations of abdominal cavity are analyzed. They were submitted to miniinvasive paracentetic drain surgical interventions under ultrasonic control. The pseudocysts of pancreas were in 16 patients, abscesses of abdominal cavity - in 2 patients. Research results. Intraoperative complications were not marked. Postoperative complications were observed in 5 patients. Among them there were inadequate drainage of all cavities of multicamerate abscess of the liver in 2 patients, progress of sacculated uremic peritonitis developing in presence of ascites in one patient, and arrosive hemorrhage in the cavity of pancreas pseudocyst in 2 persons. It is determined that it is necessary to include the spiral computer tomography to the complex of preoperative inspection of patients that allows to diagnose multicamerate abscess of the liver in time and to drain all the additional cavities adequately. 2 patients after paracentetic drain surgical interventions concerning the pseudocyst of pancreas complicated by the arrosive bleeding, were exposed to an open method before operations, related to the internal or external drain of cystic formations. Subsequently pain relapsed in their epigastric area, and the plural cysts of pancreas and retroperitoneum were found out at ultrasonic reexamination and computer tomography. In most patients analysis of liver abscess content showed E.Coli most sensible to carbapenems and cephalosporins of IV generation. Conclusions. The miniinvasive percutaneous paracentetic drain surgical interventions under ultrasonic control are effective enough in treatment of liver abscess and pseudocysts of pancreas, and accompanied by the few complications. Multicamerate liver abscesses are the relative contraindications for these operations. It is not recommended to apply paracentetic drain surgical interventions for patients who had ineffective operations of internal or external drain of pancreatic pseudocyst, in case of plural cysts . These patients have a high risk of the arrosive bleeding. Empiric antibacterial therapy in case of liver abscess before the result of bacterial analysis, must be based on the use of wide spectrum antibiotics, mainly carbapenems and cephalosporin of IV generation.